Seasonal trends in oto-rhino-laryngology outpatient clinics in the North Indian state of Punjab: a 3 year pilot study - Munjal, Manish; Kaur, Japneet; Rishi, Porshia; Tuli, Nitika; Sidhu, Harjinder; Munjal, Shubham; Nagpal, Japsimran Singh (International Journal Of Community Medicine And Public Health, 2020)
Background: Otorhinolaryngological disorders are amongst the common reason for seeking medical advice in health care setup. This study was conducted in a tertiary care hospital and medical college in North India. The monthly records of 93438 patients were analysed over a period of 3 years from January 2016 to December 2019. All monthly outpatient visits for ear nose throat (ENT) ailments, in the state with extremes of weather were recorded. No such epidemiological data about the attendance rates of patients to outpatient department (OPD) with respect to changing seasonal patterns is available. The aim of this study was to identify the various trends in the attendance pattern of ENT outpatient clinics with respect to the changes in the seasons. Methods: The monthly record of 93438 patients attending the general and speciality outpatient clinics of Dayanand Medical College, Ludhiana were studied. The study period was from January 2017 to December 2019). Results: A total of 93438 patients attended ENT OPD in three years from 2017 to 2019. Male: female ratio as 1.22:190. 1 percent of the patients belonged to 3rd and 4th decade of life , 9.9 percent of the patients were children. Patients from rural background comprised (63.1%) of the total number of patients The summer months of July, September have shown the maximum attendance during the year. The winter months of February and December have shown minimum attendance. Conclusions: Maximum patient visits were recorded in the month of July and minimum during the winter months of November to February.